Pancreatic cancer: Emerging field of regulatory B-cell-targeted immunotherapies - Senturk, Zeynep Nur; Akdag, Isilay; Deniz, Bahar; Sayi-Yazgan, Ayca (Frontiers in Immunology, 2023)
Pancreatic ductal adenocarcinoma (PDAC), the most common type of pancreatic cancer, is characterized by a high mortality rate and poor prognosis. Current treatments for PDAC, are ineffective due to a prominent immunosuppressive PDAC tumor microenvironment (TME). Although B lymphocytes are highly infiltrated into PDAC, the importance of B lymphocytes in tumorigenesis is largely neglected. B cells play a dual role in the PDAC tumor microenvironment, acting as either anti-tumorigenic or pro-tumorigenic depending on where they are localized. Tumor-infiltrating B cells, which reside in ectopic lymph nodes, namely tertiary lymphoid structures (TLS), produce anti-tumor antibodies and present tumor antigens to T cells to contribute to cancer immunosurveillance. Alternatively, regulatory B cells (Bregs), dispersed inside the TME, contribute to the dampening of anti-tumor immune responses by secreting anti-inflammatory cytokines (IL-10 and IL-35), which promote tumor growth and metastasis. Determining the role of Bregs in the PDAC microenvironment is thus becoming increasingly attractive for developing novel immunotherapeutic approaches. In this minireview, we shed light on the emerging role of B cells in PDAC development and progression, with an emphasis on regulatory B cells (Bregs). Furthermore, we discussed the potential link of Bregs to immunotherapies in PDAC. These current findings will help us in understanding the full potential of B cells in immunotherapy.